Indexing with Excel, Part 2. Checking indexing data. (1st December 2022) - Greulich, Walter
Abstract : The first article in this series showed how a Microsoft Excel table can be converted into a database. Excel's database capabilities are a prerequisite for the program to be used meaningfully in indexing. Furthermore, it was shown that in order to sort data professionally, additional fields have to be created in Excel, which are used to prepare the sorting according to internationally recognised rules. After Excel has been set up in this way, checks can be made on indexes, among other things. In order to be able to carry out such checks, further fields must be included in Excel, which are filled with special check formulae. The current article in the series focuses on the topic of checks and how sensible formulae can be developed. Through detailed examples and illustrations it shows that Excel can be used for checks similar to those in DIPs (dedicated indexing programs), but that much more is also possible.